Coronavirus Disease 2019: A Brief Review of the Clinical Manifestations and Pathogenesis to the Novel Management Approaches and Treatments - Kooshkaki, Omid; Derakhshani, Afshin; Conradie, Andelé Marie; Hemmat, Nima; Barreto, Savio George; Baghbanzadeh, Amir; Singh, Pankaj Kumar; Safarpour, Hossein; Asadzadeh, Zahra; Najafi, Souzan; Brunetti, Oronzo; Racanelli, Vito; et al. (Frontiers in Oncology, 2020)
The recent outbreak of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) or coronavirus disease 2019 (COVID-19) in China, which spread to the rest of the world, led the World Health Organization to classify it as a global pandemic. COVID-19 belongs to the Bettacoronavirus genus of the Coronaviridae family, and it mainly spreads through the respiratory tract. Studies have now confirmed a human-to-human transmission as the primary pathway of spread. COVID-19 patients with a history of diseases such as respiratory system diseases, immune deficiency, diabetes, cardiovascular disease, and cancer are prone to adverse events (admission to the intensive care unit requiring invasive ventilation or even death). The current focus has been on the development of novel therapeutics, including antivirals, monoclonal antibodies, and vaccines. However, although there is undoubtedly an urgent need to identify effective treatment options against infection with COVID-19, it is equally important to clarify management protocols for the other significant diseases from which these patients may suffer, including cancer. This review summarizes the current evidence regarding the epidemiology, pathogenesis, and management of patients with COVID-19. It also aims to provide the reader with insights into COVID-19 in pregnant patients and those with cancer, outlining necessary precautions relevant to cancer patients. Finally, we provide the available evidence on the latest potent antiviral drugs and vaccines of COVID-19 and the ongoing drug trials.